Design and Applications of Extracellular Matrix Scaffolds in Tissue Engineering and Regeneration - Sylvia Mangani; Marios Vetoulas; Katerina Mineschou; Konstantinos Spanopoulos; Maria dM. Vivanco; Zoi Piperigkou; Nikos K. Karamanos (Cells)
Tissue engineering is a growing field with multidisciplinary players in cell biology, engineering, and medicine, aiming to maintain, restore, or enhance functions of tissues and organs. The extracellular matrix (ECM) plays fundamental roles in tissue development, maintenance, and repair, providing not only structural support, but also critical biochemical and biomechanical cues that regulate cell behavior and signaling. Although its specific composition varies across different tissue types and developmental stages, matrix molecules influence various cell functional properties in every tissue. Given the importance of ECM in morphogenesis, tissue homeostasis, and regeneration, ECM-based bioscaffolds, developed through tissue engineering approaches, have emerged as pivotal tools for recreating the native cellular microenvironment. The aim of this study is to present the main categories of these scaffolds (i.e., natural, synthetic, and hybrid), major fabrication techniques (i.e., tissue decellularization and multidimensional bioprinting), while highlighting the advantages and disadvantages of each category, focusing on biological activity and mechanical performance. Scaffold properties, such as mechanical strength, elasticity, biocompatibility, and biodegradability are essential to their function and integration into host tissues. Applications of ECM-based bioscaffolds span a range of engineering and regenerative strategies, including cartilage, bone, cardiac tissue engineering, and skin wound healing. Despite promising advances, challenges remain in standardization, scalability, and immune response modulation, with future directions directed towards improving ECM-mimetic platforms.